2019
DOI: 10.1680/jphmg.16.00026
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction flow slides in large flumes

Abstract: Liquefaction flow slides in sand have been investigated during an extensive experimental research programme during the period 1973–1977 on behalf of the design of the storm surge barrier in the Oosterschelde estuary. The programme included more than a hundred tests in large- and medium-sized flumes on submerged, loosely packed sand bodies. Each sand body had a horizontal surface and a very steep, supported slope as initial boundaries. Retrogressing liquefaction flow slides with high retrogression velocity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…It should be noted that boundary effects would be expected from the low end of the strongbox which would prohibit moving of liquefied sand. It is expected that a larger scale in length would give a gentler after failure (De Groot et al 2019). Considering that W_0.01_10g and W_0.1_10g did not fail up to the maximum tilting angle of the set-up (20°) while all other tests failed before reaching the limitation (Table 2), it can be concluded that the boundary effects play an important role in the post-failure behaviour of flow slides but barely influence the samples before the onset of liquefaction.…”
Section: Resultsmentioning
confidence: 96%
“…It should be noted that boundary effects would be expected from the low end of the strongbox which would prohibit moving of liquefied sand. It is expected that a larger scale in length would give a gentler after failure (De Groot et al 2019). Considering that W_0.01_10g and W_0.1_10g did not fail up to the maximum tilting angle of the set-up (20°) while all other tests failed before reaching the limitation (Table 2), it can be concluded that the boundary effects play an important role in the post-failure behaviour of flow slides but barely influence the samples before the onset of liquefaction.…”
Section: Resultsmentioning
confidence: 96%
“…If the equilibrium of the slope is disrupted for any reason, such as climate change, erosion, or coastal flow slides, these structures may become ineffective (Aydoğan and Ayat, 2018;Cloutier et al, 2017;Stoutjesdijk et al, 1995;Guneroglu, 2015). Hence the movement of the seabed, coastal structures, and renewable wave energy devices can be negatively impacted (De Groot et al, 2012;Luijendijk et al, 2018;Ozkan and Mayo, 2019).…”
Section: Locationmentioning
confidence: 99%
“…At that time, the flow slide mechanism was generally believed to be static liquefaction and despite Barentsen's arguments the term 'zettingsvloeiing' came into use as a synonym for coastal flow slide [20,21]. Research for the Delta works in large scale flume tests in the 1970s and later, focused on rapid liquefaction failures and prevention measures in loosely packed sands [22][23][24]. Flow slides like those observed in Zeeland however, have never been demonstrated in flume tests.…”
Section: Liquefaction or Breaching?mentioning
confidence: 99%